Research on Rejuvenation of Styrene-Butadiene-Styrene Block Copolymer Modified Asphalt with Rejuvenating Agent Based on Pre-Mixing Method. (11th August 2022) - Wang, Rui; Wu, Hongjuan; Zhang, Wei; Chen, Chengqin
Abstract : The traditional addition method of rejuvenating agent used in the laboratory is inconsistent with the actual situation of the project, which reduces the reliability of the test results. In this paper, the way of premixing rejuvenating agent and Reclaimed Asphalt Pavement (RAP) and extracting asphalt binder is selected, and the modification effect, mechanism, and optimal content of rejuvenating agent on Styrene-Butadiene-Styrene Block Copolymer (SBS) modified asphalt are studied. In this paper, the asphalt in RAP is recycled and restored with different content of regenerant, and the conventional technical performance and Performance Graded (PG) grade of regenerated asphalt was tested. The composite equation of regenerated viscosity of SBS-modified asphalt was analyzed, and the pavement performance of regenerated SBS-modified asphalt mixture with different content of rejuvenating agent and RAP was tested, such as high-temperature stability, low-temperature crack resistance, and water stability. Finally, the determination method of the optimal content of rejuvenating agent was discussed. The results show that it is reliable to predict the viscosity, penetration, and softening point of regenerated asphalt by viscosity logarithmic composite equation. The content of rejuvenating agent has a certain influence on the PG classification of SBS-modified asphalt, which is mainly reflected in the low-temperature critical temperature. There is a certain content of rejuvenating agent to make the high-temperature stability of regenerated SBS-modified asphalt mixture reach the maximum. When the content of rejuvenating agent reaches a certain value, the low-temperature crack resistance and water stability of regenerated SBS-modified asphalt mixture no longer increase significantly with the increase of the content of regenerant. Using the three-level determination method of the optimal content of rejuvenating agent proposed in this paper, the optimal content and reasonable content range of rejuvenating agent can be obtained, which makes the technical performance of regenerated asphalt, PG grade, and the pavement performance of regenerated SBS-modified asphalt mixture meet the specification requirements.